PENGARUH CURRENT RATIO (CR) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP PERTUMBUHAN LABA PADA PT IMPACK PRATAMA INDUSTRI TBK PERIODE 2014-2023 - Adinda Nurul Janah; Hadijah Febriana (Journal of Research and Publication Innovation, 2024)
This study, titled "The Effect of Current Ratio (CR) and Total Asset Turnover (TATO) on Profit Growth at PT Impack Pratama Industri Tbk for the Period 2014-2023," aims to test and obtain empirical evidence regarding the effects of Current Ratio (CR) on profit growth at PT Impack Pratama Industri Tbk for the period 2014-2023, the effect of Total Asset Turnover (TATO) on profit growth at PT Impack Pratama Industri Tbk for the period 2014-2023, and the combined effect of Current Ratio (CR) and Total Asset Turnover (TATO) on profit growth at PT Impack Pratama Industri Tbk for the period 2014-2023. The type of research used is descriptive. The analysis methods employed in this research include: descriptive statistics, classical assumption tests, quantitative analysis, correlation coefficients, coefficient of determination, t-tests, and F-tests using IBM SPSS Version 26. The variables in this study are: X1 (Current Ratio), X2 (Total Asset Turnover), and Y (Profit Growth). The data used in the research is obtained from the Indonesia Stock Exchange for PT Impack Pratama Industri Tbk for the period 2014 – 2023. The data analysis technique uses t-tests and F-tests for hypothesis testing. The results of this study indicate that: 1) Current Ratio does not affect profit growth. This is evidenced by the t-test calculation with a t-value of 1.293 < t-table of 2.306 and a significance value of 0.237 > 0.05. 2) Total Asset Turnover affects profit growth. This is evidenced by the t-test calculation with a t-value of 2.826 > t-table of 2.306 and a significance value of 0.026 < 0.05. 3) Both Current Ratio and Total Asset Turnover affect profit growth. This is evidenced by the F-test calculation with an F-value of 5.349 > F-table of 4.74 and a significance value of 0.039 < 0.05.